2016
DOI: 10.1371/journal.pone.0168061
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Radiation Therapy Alone for HPV Related Oropharyngeal Cancers with High Risk Features

Abstract: BackgroundCurrent standard of care for oropharyngeal cancers with positive surgical margins and/or extracapsular extension is adjuvant chemoradiotherapy. It is unknown whether HPV+ oropharyngeal cancer benefits from this treatment intensification.ObjectiveTo investigate the outcomes of HPV+ patients treated with adjuvant radiotherapy alone when chemoradiotherapy was indicated based on high risk pathological features. They were compared with high risk HPV+ patients treated with adjuvant chemoradiotherapy.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…The extent of ECS was not graded for this study; however, in a previous publication that included nearly all patients from the current study cohort, application of ECS grading showed the highest grade of ECS (graded STM) to associate with reduced DFS. Administration of adjuvant therapy associated with improved DFS, and reduced number of recurrences correlative with our recently published matched study by Jackson et al However, addition of chemotherapy to postoperative radiation did not associate with additional benefit corroborating findings from the thesis and other reports on HPV‐related OPSCC, some of which include national cancer database analyses . The median (range) adjuvant radiation dose at the primary, ipsilateral, and contralateral neck in our study cohort was 66 (48–70), 66 (36–70), and 56 (45–66) grays (Gy).…”
Section: Discussionsupporting
confidence: 90%
“…The extent of ECS was not graded for this study; however, in a previous publication that included nearly all patients from the current study cohort, application of ECS grading showed the highest grade of ECS (graded STM) to associate with reduced DFS. Administration of adjuvant therapy associated with improved DFS, and reduced number of recurrences correlative with our recently published matched study by Jackson et al However, addition of chemotherapy to postoperative radiation did not associate with additional benefit corroborating findings from the thesis and other reports on HPV‐related OPSCC, some of which include national cancer database analyses . The median (range) adjuvant radiation dose at the primary, ipsilateral, and contralateral neck in our study cohort was 66 (48–70), 66 (36–70), and 56 (45–66) grays (Gy).…”
Section: Discussionsupporting
confidence: 90%
“…Although patients treated with chemoradiotherapy alone can be stratified into deintensification groups, pathologic staging information is not obtained, and the potential opportunity to spare them from radiotherapy is lost without that information. In a recent multicenter study, it was reported that 22% of subjects were upstaged and 13% downstaged after surgery indicating the value of pathologic information in this setting [43]. In addition, more recent data indicate that the prognostic impact of the number of cervical lymph nodes appears less important than previously believed [44–46].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the significant number of reports, the exact role of surgery still remains to be elucidated [50, 51]. Single‐institution data on omission of chemotherapy for patients have indicated that oncologic results are similar, with improved toxicity [43, 50–53]. However, these results must be interpreted cautiously, given the careful patient selection in surgical cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Although our study does not fulfill all criteria for a biomarker study (REMARK criteria; ref. 47), it is the largest (53,54). Of course, this study also has its limitations; our targeted NGS design relies on the parallels between VC and HNC.…”
Section: Discussionmentioning
confidence: 99%